2019
DOI: 10.3390/met9010050
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Process Window to Predict Hardness in Tailored Tool Thermomechanical Treatment and its Application

Abstract: Recently, in order to improve crashworthiness and achieve weight reduction of car body, a hot stamping process has been applied to the production of the part with tailored properties using tailored tool thermomechanical treatment. In the tailored tool thermomechanical treatment process, process parameters influence the mechanical properties of final product such as strength and hardness. Therefore, the prediction of hardness for final product is very important to manufacture hot-stamped part considering variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Figures 8a, 8b and 8c show, respectively, the process window to predict hardness, tensile strength and rupture deformability of low strength region for investigated quenching parameters. It has been found that the hardness decreases as the quenching time increases, in agreement to the results of Palmieri et al [15] and Kim et al [14]. Moreover, for low values of the quenching time, the hardness decreases as the temperature of the heated tools increases.…”
Section: Process Window -Ann Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Figures 8a, 8b and 8c show, respectively, the process window to predict hardness, tensile strength and rupture deformability of low strength region for investigated quenching parameters. It has been found that the hardness decreases as the quenching time increases, in agreement to the results of Palmieri et al [15] and Kim et al [14]. Moreover, for low values of the quenching time, the hardness decreases as the temperature of the heated tools increases.…”
Section: Process Window -Ann Resultssupporting
confidence: 89%
“…They exploited the theoretical model to estimate the martensite fraction on the formed part at the end of Press-Hardening process, which was numerically simulated in DYNAFORM. Kim et al [14] used FE simulation coupled with quench factor analysis to determine the process window adopted to predict hardness for different quenching time and tool temperature. In general, current scientific research aims at improving the prediction of mechanical properties by combining numerical simulations with experimental investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the low resistance force and the high formability of steel during hot forming can solve the problems of severe wearing and short life of die mold, which are common in the cold forming of high-strength steels [6]. To further improve crashworthiness and lightweight, hot-formed parts with tailored properties can be synthesized using different process control strategies, such as using a furnace with areas maintained at different temperatures and using tools with different temperatures or with different materials having different thermal conductivities [20,[37][38][39].…”
Section: Advantages and Disadvantages Of Hot Formingmentioning
confidence: 99%